Arab Christians in British Mandate Palestine : communalism and nationalism, 1917-1948 - Haiduc-Dale, Noah (Edinburgh University Press, 2013)
"Palestine's Arab Christian minority actively engaged with the Palestinian nationalist movement throughout the period of British rule (1917-1948). Relations between Muslim and Christian Arabs were sometimes strained, yet in Palestine, as in other parts of the world, communalism became a specific response to political circumstances. While Arab Christians first adopted an Arab nationalist identity, a series of outside pressures -- including British policies, the rise of a religious conflict between Jews and Muslims, and an increase in Islamic identification among some Arabs -- led Christians to adhere to more politicized religious groupings by the 1940s. Yet despite that shift Christians remained fully nationalist, insisting that they could be both Arab and Christian"--